Pengaruh Kompetensi Manajerial dan Kompetensi Kepribadian Kepala Sekolah Terhadap Kinerja Guru Sekolah Dasar Negeri di Gugus Blang Bintang Kabupaten Aceh Besar - Boyzami, Boyzami; Musdiani, Musdiani; Syarfuni, Syarfuni; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze and describe the influence of managerial competence and personality competence of school principals on the performance of State Elementary School teachers in the Blang Bintang State Elementary School Cluster, Aceh Besar Regency. This research uses a quantitative approach with an ex post facto design. The results of the research prove that there is a positive and significant influence on the performance of State Elementary School teachers in the Blang Bintang Cluster, Aceh Besar Regency with a relative contribution of 67.3% and an effective contribution of 38.1%. Personality competency has a positive and significant influence on the performance of State Elementary School teachers in the Blang Bintang Cluster, Aceh Besar Regency with a relative contribution of 32.7% and an effective contribution of 18.6%. The influence of the principal's managerial competence and personality competence simultaneously have a positive and significant influence on the performance of State Elementary School teachers in the Blang Bintang Cluster, Aceh Besar Regency. The percentage contribution of the two variables is shown by the coefficient of determination of 0.573, which means that the principal's managerial competence and the provision of personality competence can influence teacher performance by 56.7%.